2015
DOI: 10.1007/s00421-015-3180-2
|View full text |Cite
|
Sign up to set email alerts
|

Energetics (and kinematics) of short shuttle runs

Abstract: The calculations proposed in this study allow to estimate C of short SR based on simple measures of v max and can be utilized to develop training protocols in basketball as well as in other team sports (characterized by repeated sprints over short distances).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 24 publications
1
50
2
1
Order By: Relevance
“…Another motivation might be associated with the training level of our sample (elite players). It is well reported that athletes that practice a specific sport are accustomed to performing specific sport related actions, thus, they show higher movements economy than novices (31). Consequently, amateur players report larger benefits by specific training programs than elite athletes (7,17,31).…”
Section: A C C E P T E Dmentioning
confidence: 99%
See 3 more Smart Citations
“…Another motivation might be associated with the training level of our sample (elite players). It is well reported that athletes that practice a specific sport are accustomed to performing specific sport related actions, thus, they show higher movements economy than novices (31). Consequently, amateur players report larger benefits by specific training programs than elite athletes (7,17,31).…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…It is well reported that athletes that practice a specific sport are accustomed to performing specific sport related actions, thus, they show higher movements economy than novices (31). Consequently, amateur players report larger benefits by specific training programs than elite athletes (7,17,31). Throughout the football season it is generally reported a fitness improvement in pre-season, with a subsequently stabilization of such fitness variables in-season (18).…”
Section: A C C E P T E Dmentioning
confidence: 99%
See 2 more Smart Citations
“…RST can be implemented using either straight sprints or CODs (Taylor et al, 2016a). It is already reported that the presence of CODs can be an important physiological and mechanical stimulus (Dellal et al, 2010;Nedrehagen et al, 2015;Zamparo et al, 2015), as it is well known that athletes accustomed to performing CODs and short shuttle runs can reduce the energy demand (economy) during such specific actions (Zamparo et al, 2014(Zamparo et al, , 2015(Zamparo et al, , 2016. Therefore, including specific COD exercises in a training program can elicit greater developments in fitness components associated with neuromuscular factors such as jump, sprint and repeated sprint performance Bishop et al, 2011).…”
Section: Introductionmentioning
confidence: 99%